Multi‐instrument study of longitudinal wave structures for plasma bubble seeding in the equatorial ionosphere. Issue 5 (22nd October 2021) - Takahashi, H.; Essien, P.; Figueiredo, C. A. O. B.; Wrasse, C. M.; Barros, D.; Abdu, M. A.; Otsuka, Y.; Shiokawa, K.; Li, GuoZhu
Abstract: Large Scale Wave Structures (LSWS) in the equatorial ionospheric F‐region were observed by measuring spatial and temporal variations within detrended total electron content (dTEC) data obtained by ground‐based GNSS receivers over the South American continent. By using dTEC‐maps, we have been able to produce, for the first‐time, two‐dimensional representations of LSWS. During the period from September to December, the LSWS frequently occurred starting a few hours prior to Equatorial Plasma Bubble (EPB) development. From 17 events of LSWS observed in 2014 and 2015, wave characteristics were obtained: the observed wavelengths, periods, and the phase speeds are respectively, ~900 km, ~41 min and ~399 m/s; the waves propagated from the northeast to southeast. In some cases the front of the oscillation was meridionally aligned, extending to more than 1600 km, the first time such large extension of the wavefront has been reported. From F‐layer bottom height oscillation data, measured by ionosonde, LSWS exhibit two different vertical phase propagation modes, in‐phase and downward phase. The former mode indicates the presence of a polarization electric field in the F‐layer bottom side; the latter suggests propagation of atmospheric gravity waves. The presence of LSWS near the solar terminator, followed by the development of EPBs, suggests that the upwelling of the F‐layer bottom height produces a condition favorable to the development of Rayleigh–Taylor instability. Key Points: Large‐scale wave structures (LSWSs) of the equatorial ionosphere were observed by detrended TEC mapping. The LSWSs had long wavelengths (~900 km), meridionally extended wave fronts (1600 km), and were propagating mainly NE to SE‐wards. We found that the eastward propagating LSWSs were effective in producing Equatorial Plasma Bubbles.